Co-movement of short-term interest rates between Singapore and Malaysia. - Tan, Mark Seng Huat. (2008)
Investigates, by employing methods of cointegration and error correction models, the co-movement of short-term interbank and deposit rates in Singapore and Malaysia. The study further analyses possible causes of interest differentials between the two nations using the Interest Rate Parity Theorem.